Effects of Gamba grass (Andropogon gayanus) and Centro (Centrosema pubescens) Leaf meal diets on the growth and Haematological profile of weaner rabbits - Ekwe, O. O.; Okafor, C. O.; Effiong, O. O.; Ozung, P. O. (Nigerian Journal of Animal Science, 2025)
A study was conducted to investigate the potentials of two tropical African forages – Andropogon gayanus (Ag) and Centrosema pubescens (Cp) as alternative feed ingredients as replacement for maize and to evaluate the effects of diets containing these two forages on growth and Haematological profile of rabbits. Twenty four rabbits were randomly assigned into four dietary treatment groups of 6 rabbits per treatment in a completely randomized design (CRD). Each treatment was replicated three times with 2 rabbits per replicate. Parameters evaluated were growth performance, haematological and serum biochemical indices. Results showed that there were no significant (P>0.05) differences in all the growth performance indicators and Haematological indices. There were significant (P<0.05) differences in all the serum biochemical indices studied ecept Alanine amino transaminase (ALT) and very low density lipo-protein (VLDL).Albumin ranged from (30.00 - 31.30) and Creatinine ranged from (45.04 - 46.06) which were within the acceptable values respectively. Result showed that the inclution of Ag and Cp leaf meals in the diets of weaner rabbits at 5 - 15% levels. Conclusively, Ag and Cp leaf meals can be incorporated to an optimal level of 15% in rabbits feed without compromising their health. Therefore leaf meals can be used to replace maize in the diets of weaner rabbits without any deleterious effect on the haematological (blood) and serum biochemical indices.